1995
DOI: 10.1007/bf01447090
|View full text |Cite
|
Sign up to set email alerts
|

A multisystems analysis of adolescent suicide attempters

Abstract: The present study tested an ecologically based model, which predicted that hopelessness (individual level) mediates the effects of family dysfunction (interpersonal level) and socioeconomic status (sociocultural level) on both suicidal intent and suicidal ideation, within a sample of attempters. Subjects included adolescent males and females presenting at a general hospital emergency room following suicide attempts. Baron and Kenny's (1986) criteria for testing mediation models through multiple-regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…For instance, Hovey and King (1996) found that among Hispanic high school adolescents, FAD global family dysfunction was not related to suicidal ideation directly but was a significant predictor of ideation in a model that also included adolescents' expectations for the future. Similarly, Levy, Jurkovic and Spirito (1995) revealed a significant pathway between combined FAD subscales of family dysfunction and communication, hopelessness, and ideation, although no significant direct relation between the combined FAD scale and suicidal ideation was observed. This study aimed to more thoroughly examine family functioning and adolescents' suicidal ideation in a risk factor model that included global family dysfunction, family communication, and problem solving as well as multiple domains of psychopathology.…”
mentioning
confidence: 87%
“…For instance, Hovey and King (1996) found that among Hispanic high school adolescents, FAD global family dysfunction was not related to suicidal ideation directly but was a significant predictor of ideation in a model that also included adolescents' expectations for the future. Similarly, Levy, Jurkovic and Spirito (1995) revealed a significant pathway between combined FAD subscales of family dysfunction and communication, hopelessness, and ideation, although no significant direct relation between the combined FAD scale and suicidal ideation was observed. This study aimed to more thoroughly examine family functioning and adolescents' suicidal ideation in a risk factor model that included global family dysfunction, family communication, and problem solving as well as multiple domains of psychopathology.…”
mentioning
confidence: 87%
“…Studies also showed that hopelessness mediated the relationship between problem-solving deficits and suicidal ideation (Dixon et al, 1994;Miros, 2000) and Pinto et al (1996) supported a mediating model in which hopelessness contributed to negative affect, 7 which ultimately influenced suicidal ideation. However, the mediating role of hopelessness was not fully supported in other studies (e.g., Levy et al, 1995).…”
mentioning
confidence: 66%
“…Current literature on deliberate self-harm includes some extreme examples of the medical model (Abbar et al 1995) and some exclusively sociological formulations Maris 1997). But the most widely accepted approach is an integration of these two (see, for example, Levy, Jukovic & Spirito 1995;Gould et al 1996;Moscicki 1997). There is, however, no one model offering a clear causal pathway from known social risk factors for populations (for example, unemployment, homelessness) to known individual medical/psychiatric risk factors (for example, hopelessness, alcohol abuse, depression).…”
Section: Introductionmentioning
confidence: 99%